Implementasi Sistem Reverse Vending Machine (RVM) Berbasis IoT Menggunakan MobileNet SSD untuk Deteksi Objek dan Mekanisme Insentif Poin pada Platform Sampahmas - Pamungkas, Gilang Aryo; Persada, Andhika Giri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Efficient waste management presents a persistent challenge, particularly in the areas of waste collection and sorting. Among the contributors to environmental pollution, plastic waste stands out as one of the most significant. To address this issue, this study introduces a Reverse Vending Machine (RVM) system leveraging the Internet of Things (IoT) to automate the management of plastic bottle waste. The proposed system incorporates an incentive mechanism based on a point-reward system, wherein users earn redeemable points by depositing plastic bottles into the RVM. User authentication is facilitated through card and QR code integration, while ESP32-CAM and OpenCV technologies enable real-time bottle detection. The system's development employed the Agile methodology, which allows adaptability to evolving requirements throughout the development process. The iterative approach consisted of three primary phases core functionality development, system integration, and performance optimization. The study's outcome is the deployment of a point-based reward mechanism aimed at encouraging community involvement in plastic waste management. By providing tangible incentives, this system seeks to enhance public awareness and actively promote participation in recycling initiatives for plastic waste.